2010
DOI: 10.1177/0020764009357400
|View full text |Cite
|
Sign up to set email alerts
|

How Black African and White British Women Perceive Depression and Help-Seeking: a Pilot Vignette Study

Abstract: Differing perceptions of depression among black and white women could help explain GPs' lower detection rates of depressive problems of black women. Differences in views about the formal help available may explain ethnic differences in help-seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…It may also reflect a lack of knowledge about the illness. Interestingly, these same three dimensions also differed between White British and Black African women in an English study looking at how these minority groups perceived depression symptoms [19]. The authors concluded that these differences could help explain general practitioners' lower detection rates of depressive problems in Black African women.…”
Section: Illness Perceptionmentioning
confidence: 94%
See 2 more Smart Citations
“…It may also reflect a lack of knowledge about the illness. Interestingly, these same three dimensions also differed between White British and Black African women in an English study looking at how these minority groups perceived depression symptoms [19]. The authors concluded that these differences could help explain general practitioners' lower detection rates of depressive problems in Black African women.…”
Section: Illness Perceptionmentioning
confidence: 94%
“…The survey included a short vignette written by the authors representing a hypothetical case of a 12-year-old girl suffering from OCD symptoms (see vignette in Supplemental Material). The vignette methodology has been previously used in similar studies [19,23] and found to be very helpful in obtaining responses which resemble real-life situations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some ethnic groups are less likely to consult their GPs, as occurs with Africans 39 and Asians. 40 Even when people do attend their GP, detection rates for mental health problems are lower in ethnic minority groups.…”
Section: Health Beliefsmentioning
confidence: 99%
“…A recent study of the attitudes of black African women in London who had suffered depression found that they thought depression was less serious, more short-lasting and less amenable to treatment compared with white British women. 39 The ways in which people describe their problems also differ between cultures. For example, it is common for people from South Asia to express their problems as aches, pains, and sleep problems.…”
Section: Health Beliefsmentioning
confidence: 99%